Cryptosporidium Removal from Runoff by Active Carbon Filter with Coal Gangue. (29th June 2016) - Lu, Ping; Yuan, Tao; Zhang, Baojun
Abstract : Transport of Cryptosporidium in runoff will contaminate the surrounding water body. Cryptosporidium -sized microspheres and inactive Cryptosporidium parvum oocysts removal using an active carbon (AC) filter with/without coal gangue from the runoff was evaluated. Chemical composition of coal gangue was determined, and its performance as a water treatment material was tested. Results showed SiO2 was the dominant chemical component of coal gangue. Removal was only 20% for microspheres and 24% for oocysts by AC filtration alone. The removal for both was increased to more than 98% by addition of coal gangue powder to the filter. Furthermore, gangue reuse turned commercially worthless material to a water treatment material as well helping prevent gangue from occupying agriculture/industry land.